Fhytophysionomic analysis of two areas of seasonally dry tropical forest - Miranda, Rita Aparecida (2022)
The objective of this study was to structurally characterize the vegetation present in two different caatinga physiognomies at the Aroeira Grande municipality in Baraúna / RN. For this study, the plot method was used in which all the included individuals had height and stem diameter at the base level (DBL) ? 3 cm and ? 1 m, respectively. The species Cordia glazioviana, Croton blanchetianus, Cynophalla flexuosa, and Poincianella pyramidalis presented the highest phytosociological parameters for Area I, with 12.5% relative frequencies. Croton blanchetianus stood out with 88.12% relative density and Croton glazioviana predominated in the dominance parameter with 59.88%.dominance. In Area II, Piptadenia stipulaceae, Bauhinia cheilantha, and Cynophala flexuosa presented the highest relative frequencies, all with 7.32%. However, Croton blanchetianus stood out over the rest of the species in density (32.33%) and in dominance (17.36%). The Euphorbiaceae family was predominant in both areas.